Measuring benefits at end of life for economic evaluation: measure development and a 'thinkaloud' study. Issue 2 (1st June 2012) - Coast, J.; Sutton, E.; Orlando, R.; Armour, K.
Abstract : Introduction: NICE uses economic evaluation to determine which interventions (including symptom control) provide most benefit for the resources used. Current health-gain measures for economic analysis may miss important benefits of holistic end of life care and these interventions may not be prioritised. Aims and Methods: To develop and evaluate a new measure for economic evaluation of end of life care. In-depth interviews with 23 informants at different stages along the dying trajectory (general population, residential care, palliative care) explored what informants felt was important about end of life care, dying and death. Constant comparison was used to develop conceptual attributes; repeat interviews with 12 informants checked these attributes and generated wording for the measure. Interviews with patients (n=35), family members or carers (n=20) and health professionals (n=20) will use the 'thinkaloud' technique to study the measure's feasibility and validity. Results: Seven attributes emerged based on what people felt was important to them: autonomy, love, physical suffering, emotional suffering, dignity, support and preparation. These provide the basis for seven questions in a simple measure expressed in terms of capability, each with four levels. Thinkaloud interviews will provide important information about who could complete the measure, and an understanding of why differences occur when measures are completed by different groups. Conclusion: Rigorous methods have been used to develop a measure for use in economic evaluation that will more accurately reflect benefits of end of life care. Validation is ongoing.